An Examination of the Complexity of the Large Sociotechnical Space System - Francisco Del Canto Viterale (Aerospace, 2025)
Complexity has emerged as a global phenomenon with significant implications for the organization and structure of any system. In recent decades, the space system has undergone a transition to a more complex configuration. This essay argues that the increasing complexity of space system architecture is attributable to the proliferation and diversification of actors, interactions, processes, trends, and topics that demand novel examinations and explanations. This research emphasizes the necessity of employing systems and social science methodologies to evaluate and provide novel perspectives on the study of complex systems, such as the space system. The primary objective of this study is to examine the complex structure of the current space system using a sociotechnical systems model. The present study offers a comprehensive examination of the contemporary space system, emphasizing the role of contextual elements, active agents, forms of interaction, and the diverse applications and emergent trends that are profoundly influencing not only the space system itself but also the broader international system.